Improving The Students’ Learning Activities and Achievement in learning mathematics by Using Cooperative Model Tipe Jigsaw at S.1 PGSD FIP UNP - Mursal Dalais (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
The students of Pgsd have difficulty in learning mathematics, because of the method that is used by lecturer is not appropriate. As the result the students’ achievement in mathematics are not optimal. The researcher has used cooperative model to overcome this problem. This method is hoped to be able to improve the students’ learning activities and achievement. This research was claasroom action research. The aim of this research was to describe the students learning activities and achievement at PGSD in learning mathematics by using cooperative model Type Jigsaw. This research was divided into three cycles that consists of planning, action, observation, and reflection. The instrument of data gathering consist of observation sheets, test and questionare. The research results showed that ;The students’ activities in learning mathematics showed cooperative model, where the students have responsibility to their tasks, work together, help each other, and communicate each other. It can be concluded that the students’ learning activities and achievement in learning mathematics by using cooperative model type jigzaw at PGSD FIP UNP had improved.Consequently the mathematics lecturers at PGSD frequently use cooperative model type jigsaw in learning.